Population Growth and Investment Opportunity - Sweezy, A. R. (Quarterly Journal of Economics, 1940)
Revival of interest in the question of long-run investment opportunity, 64. — Doubts concerning population growth as an "offsetting factor, " 65. — Ways in which it might influence investment opportunity: (1) the propensity to consume, 66; (2) the composition of aggregate consumer demand, 66; (3) the supply of labor, 70; influence of competitive conditions, 72; effect of wage reductions, 73; the expanding economy, 74; labor supply a limiting rather than an initiating factor, 75; (4) broader phenomena affecting investment, 77.